Assessment of South-South cooperation and the global narrative on the eve of BAPA+40 - Yuefen Li (South Centre, 2018)
This research paper gives a brief account of the fast expansion of South-South cooperation (SSC) in volume, modalities and participating countries and institutions. Though SSC is a de facto development compact, there is a tendency to overstate the total concessional financial element of SSC compared to Official Development Assistance (ODA), as SSC constitutes only a small portion of the total ODA from traditional donors. North-South cooperation (NSC) is still the dominant pillar of development finance; hence SSC needs to be regarded as a complement to and not a substitute for NSC. In view of its relatively short history of economic and financial cooperation as well as technical assistance projects, SSC is facing many challenges including the lack of soft and hard institutional frameworks. With a realistic assessment of SSC and its global narrative, and taking into account the growing diversity among the Southern countries as providers and users of SSC, the paper makes suggestions on important elements that the coming Second High-Level United Nations Conference on South-South Cooperation may consider to consolidate the Southern ownership of SSC and enhance its impact on achieving the Sustainable Development Goals.
Keywords: 300; Entwicklungshilfe; Internationale Wirtschaftsbeziehungen; Süd-Süd-Beziehungen; Welt